Strengthening Sociopreneurship of Sugar Palm Farmers in Langke Village Gentuma Raya District, Gorontalo Province - Mardin, Herinda; Taan, Hapsawati; Hasan, Fardyansjah; Anas, Muhammad; Sudiarta, I Made; Hasanuddin, Hasanuddin; Dako, Amirudin Y. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2024)
Sugar palm plants have great potential as a superior commodity that can support the community's economy, especially in rural areas. Apart from being a source of food, such as palm sugar and palm fruit, this plant also has high economic value because it can be utilized optimally from the roots, stems, leaves, and sap. Limited knowledge in business management and marketing also makes it difficult for farmers to compete with other products that are more easily accessible to consumers. These factors often cause low selling prices and suboptimal profits for sugar palm farmers. However, behind these challenges, there are a number of opportunities that can be exploited to improve the welfare of sugar palm farmers in Langke Village. One of them is the increasing market demand for natural and organic products, such as palm sugar which is healthier than granulated sugar. Apart from that, with a sociopreneurship approach, farmers can be empowered to manage their businesses more professionally, expand markets, and process other sugar palm derivative products such as palm fruit or handicraft products from sugar palm stems and leaves. With the support of training, better market access, and innovation in business management, the potential of palm trees in Langke Village can be developed to open up new economic opportunities and improve the welfare of the local community. Activities to strengthen sociopreneurship for sugar palm farmers in Langke Village are that this activity has succeeded in increasing understanding and strengthening the spirit of social entrepreneurship among farmers, encouraging them to not only pursue profits, but also have a positive impact on the surrounding community. With continued support, the potential of sugar palm plants in Langke Village can be more optimal, opening up new economic opportunities and improving community welfare.